Composite electrode wire and preparation method thereof

Through continuous extrusion and coating and drawing annealing of superplastic zinc-manganese alloy and brass core material, composite electrode wire is formed, which solves the pollution and processing difficulties in the galvanized electrode wire process, and achieves efficient and environmentally friendly slow-moving Wire discharge processing performance.

CN115401275BActive Publication Date: 2025-01-14FUJIKURA HENGTONG AERIAL CABLE SYST
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202211071651.0
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-09-02
Publication Date
2025-01-14
Estimated Expiration
2042-09-02

AI Technical Summary

Technical Problem

The existing galvanized electrode wire process has serious environmental pollution and difficult processing, especially when processing to below 0.1mm specifications, it is difficult to achieve efficient cutting and high precision.

Method used

The superplastic zinc-manganese alloy and brass core material are continuously extruded to form a composite electrode wire, and the electroplating process is avoided, and the fine grain size and high strength of zinc-manganese alloy are achieved, which is suitable for Slow-travel wire discharge processing.

Benefits of technology

The electroless plating process avoids environmental pollution. The superplasticity of zinc-manganese alloy improves processing performance and can be processed below 0.1mm specifications. The tensile strength and conductivity reach the performance of ordinary galvanized wires, expanding the application range.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0003830583730000021
    Figure BDA0003830583730000021
Patent Text Reader

Abstract

The present invention belongs to the technical field of slow-moving wire discharge machining, and specifically relates to a composite electrode wire and a preparation method thereof. A superplastic zinc-manganese alloy is produced by the method of upward continuous casting and continuous extrusion, and then the superplastic zinc-manganese alloy is coated on the surface of a brass core material as a surface layer by a continuous extrusion coating method, followed by wire drawing and annealing treatment, and processed to the target specification, so that the core material and the surface layer form a composite electrode wire. The continuous extrusion coating method solves the problem of environmental pollution caused by the existing galvanized wire process, and the superplastic zinc-manganese alloy has excellent processing performance, which solves the problem of difficulty in later processing to specifications below 0.1mm.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of slow-wire electric discharge machining, and specifically relates to a composite electrode wire and a preparation method thereof. Background Art

[0002] Wire EDM uses a continuously moving wire as an electrode to perform pulsed spark discharge to remove metal from the workpiece, and finally processes it into shape according to the set trajectory. Galvanized wire is a type of electrode wire used for wire EDM. The zinc is coated on the surface of the core material by electroplating or hot-dip plating. The purpose is to use the gasification of zinc during the EDM process to stabilize the discharge of the electrode wire, achieve high cutting efficiency, high surface finish of the cut workpiece, and high dimensional accuracy. However, this type of electrode wire has the problem of serious pollution during the processing and difficulty in processing to finer specifications.

[0003] The invention patent with patent application number CN113909599A discloses a method for manufacturing galvanized electrode wire. The manufacturing method includes melting, giant drawing, annealing, large drawing, medium drawing, electroplating and small drawing. The electroplating process is to perform alkaline electrolysis, first water washing, acid electrolysis, second water washing, two consecutive electrogalvanizing, drying and wire winding on the brass wire billet (i.e. core material) in sequence. The galvanized electrode wire produced by this process can further improve the cutting efficiency, workpiece size accuracy and surface finish.

[0004] The above patent discloses a method for manufacturing galvanized electrode wire, which uses electroplating to cover the surface of the core material with zinc. This method causes serious environmental pollution. At the same time, zinc has a close-packed hexagonal crystal structure and is difficult to process. It is difficult to process it to a specification below 0.1mm in the later stage.

[0005] The invention patent with patent application number CN113823435A discloses a composite electrode wire, a preparation method of the composite electrode wire and its application. The method directly covers the outer brass tubular outer material on the outer surface of the conductive alloy core material, and then performs pressure cold packing, so that the conductive alloy core material and the brass outer material are directly and concentrically coated into one, and then through drawing, annealing and wire drawing, the core material and the outer material form the final composite electrode wire. The surface of the composite electrode wire can be sprayed with a zinc material coating, which solves the technical problems of the existing composite electrode wire having a dull surface and low overall strength.

[0006] The above patent discloses a composite electrode wire, a preparation method of the composite electrode wire and its application. This process solves the problem of dull surface and low overall strength of the electrode wire, but does not solve the problem of environmental pollution and processing difficulties caused by the galvanized wire process. Summary of the invention

[0007] In view of the above problems, the present invention provides a method for preparing a composite electrode wire, comprising the following steps:

[0008] S1: Mixing metal zinc and metal manganese, smelting, and upward continuous casting to obtain a zinc-manganese alloy upward rod;

[0009] S2: continuously extruding the zinc-manganese alloy upper rod to obtain a zinc-manganese alloy extruded rod; the number of continuous extrusions is 5-10 times, the deformation amount of each extrusion is 0-99%, and the deformation amount of the first extrusion is greater than 80%;

[0010] S3: using a brass rod as an inner core and two zinc-manganese alloy extruded rods as outer layers, and obtaining a composite material after extrusion coating; the ratio of the cross-sectional area of ​​the brass rod to the cross-sectional area of ​​the composite material is 1:1.01-1.10;

[0011] The sum of the cross-sectional areas of the two zinc-manganese alloy extruded rods is greater than the cross-sectional area of ​​the brass rod;

[0012] S4: performing wire drawing annealing on the composite material to obtain the composite electrode wire;

[0013] The mass fraction of zinc in the zinc-manganese alloy upper lead rod is 99.00-99.99%.

[0014] Preferably, in step S1, the smelting temperature is 600-700°C.

[0015] Preferably, in step S1, the speed of upward continuous casting is 0.5-1.5 m / min.

[0016] Preferably, in the step S1, an antioxidant is applied after the upward continuous casting; the antioxidant comprises an amino acid salt of methylbenzotriazole and water.

[0017] The antioxidant was purchased from Suzhou Yuanyue Mechanical and Electrical Equipment Automation Co., Ltd. The structural formula of the amino acid salt of methylbenzotriazole is as follows:

[0018]

[0019] Wherein, R is selected from methyl, ethyl, propyl, isopropyl, butyl, isobutyl or tert-butyl.

[0020] Furthermore, the mass ratio of the amino acid salt of methylbenzotriazole to water is 1:10-100.

[0021] Preferably, in step S2, the temperature of continuous extrusion is 200-300°C.

[0022] Preferably, in step S2, the rotation speed of the extrusion wheel for continuous extrusion is 0.1-5 rpm.

[0023] Preferably, in step S3, the extrusion coating is performed using a continuous extrusion coating machine, and the coating speed is 10-200 m / min.

[0024] Furthermore, the spacing between the coating module and the guide die of the continuous extrusion coating machine is 6-7 mm, and the gap of the guide die is 0.6-1.8 mm.

[0025] Preferably, the copper content of the brass rod is 60-65wt%, with the remainder being Zn and other inevitable impurities.

[0026] Preferably, the cross-sectional area of ​​the brass rod is smaller than the sum of the cross-sectional areas of the two zinc-manganese alloy extruded rods.

[0027] Preferably, in step S4, the wire drawing annealing adopts a continuous wire drawing machine, the annealing voltage is 30-40V, and the drawing speed is 300-1000m / min.

[0028] Furthermore, the composite material is sequentially passed through a large continuous drawing machine, a medium continuous drawing machine, a small continuous drawing machine and a micro continuous drawing machine to be drawn to the target specification.

[0029] The present invention also provides a composite electrode wire prepared by the above-mentioned preparation method, and the composite electrode wire can be used in the field of slow-moving wire discharge machining.

[0030] The superplastic zinc-manganese alloy is made by continuous casting and extrusion, and then the superplastic zinc-manganese alloy is coated on the surface of the brass core material by continuous extrusion coating. After that, the wire drawing and annealing are performed to process the target specifications, so that the core material and the surface layer form a composite electrode wire. The continuous extrusion coating method solves the environmental pollution problem of the existing galvanized wire process. The superplastic zinc-manganese alloy has excellent processing performance and solves the problem of difficulty in later processing to specifications below 0.1mm.

[0031] The technical solution of the present invention has the following advantages over the prior art:

[0032] (1) The present invention has no electroplating process and is environmentally friendly;

[0033] (2) After being processed by a special process, the zinc-manganese alloy on the surface of the present invention has fine grains, an average grain size of less than 1 μm, and superplasticity. Compared with pure zinc, it has better processing performance, which is conducive to processing the overall composite material to a diameter of less than 0.1 mm, thereby expanding its application in the field of wire-cut electrical discharge machining;

[0034] (3) The composite material of the present invention has a tensile strength of >900 MPa and a conductivity of >19% IACS, and can achieve the performance of ordinary galvanized wire under the same specifications. DETAILED DESCRIPTION

[0035] The present invention is further described below in conjunction with specific embodiments so that those skilled in the art can better understand the present invention and implement it, but the embodiments are not intended to limit the present invention.

[0036] Example 1

[0037] A composite electrode wire provided by an embodiment of the present invention comprises: a core material and a surface layer;

[0038] The core material is ordinary brass;

[0039] The surface layer is a zinc-manganese alloy with superplasticity;

[0040] A method for preparing the above-mentioned composite electrode wire comprises the following steps:

[0041] (1) Preparing a zinc-manganese alloy extruded rod having superplasticity required for a surface layer comprises the following steps:

[0042] a. Upward continuous casting: 99.1% zinc and 0.9% manganese by weight are put into an upward continuous casting furnace and smelted at 600°C. Then, a zinc-manganese alloy upward rod with a diameter of 14mm is cast at a traction speed of 0.5m / min. When winding, an antioxidant is coated on the surface, and the ratio of antioxidant to water is 1:10;

[0043] b. Continuous extrusion: The zinc-manganese alloy upper guide rod with a diameter of 14 mm was continuously extruded 10 times, wherein the cavity preheating temperature was 200°C, the extrusion wheel speed was 0.1 rpm, the first extrusion was to a diameter of 6 mm, the second extrusion was to a diameter of 8 mm, the third extrusion was to a diameter of 6 mm, the fourth extrusion was to a diameter of 8 mm, the fifth extrusion was to a diameter of 6 mm, the sixth extrusion was to 8 mm, the seventh extrusion was to 6 mm, the eighth extrusion was to 8 mm, the ninth extrusion was to 6 mm, and the tenth extrusion was to 6 mm;

[0044] (2) preparing an ordinary brass rod required for the core material and removing dust and grease from the surface, wherein the brass rod has a diameter of 7.4 mm, a copper content of 60 wt%, and the rest being zinc and unavoidable impurities;

[0045] (3) Continuous extrusion coating: A 7.4 mm diameter ordinary brass rod is used as the core material and two 6 mm diameter zinc-manganese alloy extruded rods are used as the surface layer through a continuous extrusion coating machine to form a composite material with a diameter of 7.5 mm. The coating speed is 10 m / min, the distance between the coating module and the guide die is 6 mm, and the guide die gap is 1.8 mm.

[0046] (4) Wire drawing and annealing: The composite material with a diameter of 7.5 mm was passed through a large drawing machine to obtain a composite material with a diameter of 3 mm, with a drawing speed of 300 m / min and an annealing voltage of 40 V; then the composite material with a diameter of 1.2 mm was passed through a medium drawing machine to obtain a composite material with a drawing speed of 500 m / min and an annealing voltage of 37 V; then the finished product with a diameter of 0.3 mm was obtained through a small drawing machine to obtain a finished product with a drawing speed of 900 m / min and an annealing voltage of 34 V.

[0047] Example 2

[0048] A composite electrode wire provided by an embodiment of the present invention comprises: a core material and a surface layer;

[0049] The core material is ordinary brass;

[0050] The surface layer is a zinc-manganese alloy with superplasticity;

[0051] A method for preparing the above-mentioned composite electrode wire comprises the following steps:

[0052] (1) Preparing a zinc-manganese alloy extruded rod having superplasticity required for the surface layer, comprising the following steps:

[0053] a. Upward continuous casting: 99.3% zinc and 0.7% manganese by weight are put into an upward continuous casting furnace and smelted at 620°C. Then, a zinc-manganese alloy upward rod with a diameter of 16 mm is cast at a traction speed of 0.7 m / min. When winding, an antioxidant is coated on the surface, and the ratio of antioxidant to water is 1:30;

[0054] b. Continuous extrusion: The zinc-manganese alloy upper guide rod with a diameter of 16 mm was continuously extruded 8 times, wherein the cavity preheating temperature was 230°C, the extrusion wheel speed was 1 rpm, the first extrusion was to a diameter of 7 mm, the second extrusion was to a diameter of 5.5 mm, the third extrusion was to a diameter of 7 mm, the fourth extrusion was to a diameter of 5.5 mm, the fifth extrusion was to a diameter of 7 mm, the sixth extrusion was also to a diameter of 5.5 mm, the seventh extrusion was to a diameter of 7 mm, and the eighth extrusion was to a diameter of 5.5 mm;

[0055] (2) preparing an ordinary brass rod required for the core material and removing dust and grease from the surface, wherein the diameter of the brass rod is 7.35 mm, the copper content is 62 wt%, and the rest is zinc and unavoidable impurities;

[0056] (3) Continuous extrusion coating: A 7.35 mm diameter ordinary brass rod is used as the core material and two 5.5 mm diameter zinc-manganese alloy extruded rods are used as the surface layer to form a composite material with a diameter of 7.5 mm through a continuous extrusion coating machine. The coating speed is 30 m / min, the distance between the coating module and the guide die is 6.3 mm, and the guide die gap is 1.6 mm;

[0057] (4) Wire drawing and annealing: The composite material with a diameter of 7.5 mm was passed through a large drawing and annealing machine to obtain a composite material with a diameter of 3 mm, with a drawing speed of 350 m / min and an annealing voltage of 39 V; then the composite material with a diameter of 1.2 mm was passed through a medium drawing and annealing machine, with a drawing speed of 550 m / min and an annealing voltage of 36 V; then the finished product with a diameter of 0.25 mm was obtained through a small drawing and annealing machine, with a drawing speed of 950 m / min and an annealing voltage of 33 V.

[0058] Example 3

[0059] A composite electrode wire provided by an embodiment of the present invention comprises: a core material and a surface layer;

[0060] The core material is ordinary brass;

[0061] The surface layer is a zinc-manganese alloy with superplasticity;

[0062] The method for preparing the composite electrode wire comprises the following steps:

[0063] (1) Preparing a zinc-manganese alloy extruded rod having superplasticity required for the surface layer, comprising the following steps:

[0064] a. Upward continuous casting: 99.5% zinc and 0.5% manganese by weight are put into an upward continuous casting furnace and smelted at 640°C. Then, a zinc-manganese alloy upward rod with a diameter of 18 mm is cast at a traction speed of 0.9 m / min. When winding, an antioxidant is coated on the surface, and the ratio of antioxidant to water is 1:50;

[0065] b. Continuous extrusion: The zinc-manganese alloy upper guide rod with a diameter of 18 mm was continuously extruded 6 times, wherein the cavity preheating temperature was 250°C, the extrusion wheel speed was 3 rpm, the first extrusion was to a diameter of 8 mm, the second extrusion was to a diameter of 7.5 mm, the third extrusion was to a diameter of 7 mm, the fourth extrusion was to a diameter of 6.5 mm, the fifth extrusion was to a diameter of 6 mm, and the sixth extrusion was also to a diameter of 5.5 mm;

[0066] (2) preparing an ordinary brass rod required for the core material and removing dust and grease from the surface, wherein the diameter of the brass rod is 7.3 mm, the copper content is 63 wt%, and the rest is zinc and unavoidable impurities;

[0067] (3) Continuous extrusion coating: A 7.3 mm diameter ordinary brass rod is used as the core material and two 5.5 mm diameter zinc-manganese alloy extruded rods are used as the surface layer to form a composite material with a diameter of 7.5 mm through a continuous extrusion coating machine. The coating speed is 70 m / min, the distance between the coating module and the guide die is 6.6 mm, and the guide die gap is 1.2 mm;

[0068] (4) Wire drawing and annealing: The composite material with a diameter of 7.5 mm is passed through a large drawing and annealing machine to obtain a composite material with a diameter of 3 mm, with a drawing speed of 400 m / min and an annealing voltage of 38 V; then the composite material with a diameter of 1.2 mm is passed through a medium drawing and annealing machine, with a drawing speed of 600 m / min and an annealing voltage of 35 V; then the finished product with a diameter of 0.2 mm is obtained through a small drawing and annealing machine, with a drawing speed of 1000 m / min and an annealing voltage of 33 V.

[0069] Example 4

[0070] A composite electrode wire provided by an embodiment of the present invention comprises: a core material and a surface layer;

[0071] The core material is ordinary brass;

[0072] The surface layer is a zinc-manganese alloy with superplasticity;

[0073] The method for preparing the composite electrode wire comprises the following steps:

[0074] (1) Preparing a zinc-manganese alloy extruded rod having superplasticity required for the surface layer, comprising the following steps:

[0075] a. Upward continuous casting: 99.7% zinc and 0.3% manganese by weight are put into an upward continuous casting furnace and smelted at 660°C. Then, a zinc-manganese alloy upward rod with a diameter of 20 mm is cast at a traction speed of 1.1 m / min. When winding, an antioxidant is coated on the surface, and the ratio of antioxidant to water is 1:70;

[0076] b. Continuous extrusion: The zinc-manganese alloy upper guide rod with a diameter of 20 mm was continuously extruded 6 times, wherein the cavity preheating temperature was 270°C, the extrusion wheel speed was 4 rpm, the first extrusion was to a diameter of 8.5 mm, the second extrusion was to a diameter of 8 mm, the third extrusion was to a diameter of 7.5 mm, the fourth extrusion was to a diameter of 7 mm, the fifth extrusion was to a diameter of 6.5 mm, and the sixth extrusion was also to a diameter of 6 mm;

[0077] (2) preparing an ordinary brass rod required for the core material and removing dust and grease from the surface, wherein the diameter of the brass rod is 7.25 mm, the copper content is 65 wt%, and the rest is zinc and unavoidable impurities;

[0078] (3) Continuous extrusion coating: A 7.25 mm diameter ordinary brass rod as the core material and two 6 mm diameter zinc-manganese alloy extruded rods as the surface layer are formed into a composite material with a diameter of 7.5 mm by a continuous extrusion coating machine. The coating speed is 100 m / min, the distance between the coating module and the guide die is 6.8 mm, and the guide die gap is 1.0 mm;

[0079] (4) Wire drawing and annealing: The composite material with a diameter of 7.5 mm was passed through a large drawing machine to obtain a composite material with a diameter of 3 mm, with a drawing speed of 450 m / min and an annealing voltage of 37 V; then the composite material with a diameter of 1.2 mm was passed through a medium drawing machine to obtain a composite material with a drawing speed of 650 m / min and an annealing voltage of 35 V; then the composite material with a diameter of 0.5 mm was passed through a small drawing machine to obtain a composite material with a drawing speed of 850 m / min and an annealing voltage of 32 V; finally, a finished product with a diameter of 0.1 mm was obtained through a micro drawing machine to obtain a finished product with a drawing speed of 1000 m / min and an annealing voltage of 31 V.

[0080] Example 5

[0081] A composite electrode wire provided by an embodiment of the present invention comprises: a core material and a surface layer;

[0082] The core material is ordinary brass;

[0083] The surface layer is a zinc-manganese alloy with superplasticity;

[0084] The method for preparing the composite electrode wire comprises the following steps:

[0085] (1) Preparing a zinc-manganese alloy extruded rod having superplasticity required for the surface layer, comprising the following steps:

[0086] a. Upward continuous casting: 99.9% zinc and 0.1% manganese by weight are put into an upward continuous casting furnace and smelted at 700°C. Then, a zinc-manganese alloy upward rod with a diameter of 22mm is cast at a traction speed of 1.5m / min. When winding, an antioxidant is coated on the surface, and the ratio of antioxidant to water is 1:100;

[0087] b. Continuous extrusion: The zinc-manganese alloy upper guide rod with a diameter of 22 mm was continuously extruded 5 times, wherein the cavity preheating temperature was 300°C, the extrusion wheel speed was 5 rpm, the first extrusion was to a diameter of 8 mm, the second extrusion was to a diameter of 7.5 mm, the third extrusion was to a diameter of 7 mm, the fourth extrusion was to a diameter of 6.5 mm, and the fifth extrusion was to a diameter of 6 mm;

[0088] (2) preparing an ordinary brass rod required for the core material and removing dust and grease from the surface, wherein the brass rod has a diameter of 7.2 mm, a copper content of 63 wt%, and the rest being zinc and unavoidable impurities;

[0089] (3) Continuous extrusion coating: A 7.2 mm diameter ordinary brass rod as the core material and two 6 mm diameter zinc-manganese alloy extruded rods as the surface layer are formed into a composite material with a diameter of 7.5 mm by a continuous extrusion coating machine. The coating speed is 200 m / min, the distance between the coating module and the guide die is 7 mm, and the guide die gap is 0.6 mm;

[0090] (4) Wire drawing and annealing: The composite material with a diameter of 7.5 mm was passed through a large drawing machine to obtain a composite material with a diameter of 3 mm, with a drawing speed of 400 m / min and an annealing voltage of 37 V; then the composite material with a diameter of 1.2 mm was passed through a medium drawing machine to obtain a composite material with a drawing speed of 600 m / min and an annealing voltage of 35 V; then the composite material with a diameter of 0.3 mm was passed through a small drawing machine to obtain a composite material with a drawing speed of 800 m / min and an annealing voltage of 33 V; finally, a finished product with a diameter of 0.1 mm was obtained through a micro drawing machine to obtain a finished product with a drawing speed of 1000 m / min and an annealing voltage of 30 V.

[0091] Comparative Example 1

[0092] Commercially available galvanized wire, diameter 0.3mm.

[0093] Comparative Example 2

[0094] Commercially available galvanized wire, diameter 0.25mm.

[0095] Comparative Example 3

[0096] Commercially available galvanized wire, diameter 0.2mm.

[0097] Effect evaluation 1

[0098] The tensile strength of the finished products with a diameter of ≤0.25 mm in Examples 1 to 5 and Comparative Examples 1 to 3 was tested according to the provisions of GB / T 10537, the tensile strength of the finished products with a diameter of >0.25 mm in Examples 1 to 5 and Comparative Examples 1 to 3 was tested according to the provisions of GB / T 228.1-2010, and the conductivity of all the finished products in Examples 1 to 5 and Comparative Examples 1 to 3 was tested according to the provisions of GB / T 351. The results are shown in the following table:

[0099] Table 1 Performance test table of embodiments and comparative examples

[0100] Diameter(mm) Tensile strength(MPa) Electrical conductivity (%IACS) Example 1 0.3 928 23.6 Example 2 0.25 974 21.8 Example 3 0.2 1045 21.1 Example 4 0.1 1102 20.4 Example 5 0.07 1156 19.2 Comparative Example 1 0.3 935 23.5 Comparative Example 2 0.25 987 22 Comparative Example 3 0.2 1033 21.2

[0101] By comparing the examples and comparative examples in Table 1, it can be clearly concluded that the composite material of the present invention has a similar tensile strength and conductivity to commercially available materials at the same diameter. In addition, the present invention can be processed into specifications of 0.1 mm and below, and has excellent processing performance.

[0102] Obviously, the above embodiments are merely examples for clear explanation and are not intended to limit the implementation methods. For those skilled in the art, other different forms of changes or modifications can be made based on the above description. It is not necessary and impossible to list all the implementation methods here. The obvious changes or modifications derived from these are still within the protection scope of the invention.

Claims

1. A method for preparing a composite electrode wire, characterized in that: The steps include: S1: Mixing metal zinc and metal manganese, smelting, and upward continuous casting to obtain a zinc-manganese alloy upward rod; S2: continuously extruding the zinc-manganese alloy upper rod to obtain a zinc-manganese alloy extruded rod; the number of continuous extrusions is 5-10 times, and the deformation of the first extrusion is greater than 80%; S3: using a brass rod as an inner core and two zinc-manganese alloy extruded rods as outer layers, and obtaining a composite material after extrusion coating; the ratio of the cross-sectional area of ​​the brass rod to the cross-sectional area of ​​the composite material is 1:1.01-1.10; The sum of the cross-sectional areas of the two zinc-manganese alloy extruded rods is greater than the cross-sectional area of ​​the brass rod; S4: performing wire drawing annealing on the composite material to obtain the composite electrode wire; The mass fraction of zinc in the zinc-manganese alloy upper guide rod is 99.0-99.9%; In the step S1, the smelting temperature is 600-700°C, the speed of the upward continuous casting is 0.5-1.5 m / min, and an antioxidant is applied after the upward continuous casting; the antioxidant comprises an amino acid salt of methyl benzotriazole and water, and the mass ratio of the amino acid salt of methyl benzotriazole to water is 1:10-100; in the step S2, the temperature of continuous extrusion is 200-300°C; in the step S3, a continuous extrusion coating machine is used for extrusion coating, and the coating speed is 10-200 m / min; the copper content of the brass rod is 60-65wt%, and the remainder is Zn and other inevitable impurities; in the step S4, a continuous annealing wire drawing machine is used for wire drawing annealing, the annealing voltage is 30-40 V, and the drawing speed is 300-1000 m / min.

2. A composite electrode wire prepared by the preparation method as claimed in claim 1.

Citation Information

Patent Citations

  • Galvanized electrode wire manufacturing method

    CN113909599A

  • Composite electrode wire, and preparation method and application of composite electrode wire

    CN113823435A